Structural reorganisation of cellulose fibrils in hydrothermally deconstructed lignocellulosic biomass and relationships with enzyme digestibility - Ibbett, Roger; Gaddipati, Sanyasi; Hill, Sandra; Tucker, Gregory A. (BioMed Central, 2013)
Background: The investigation of structural organisation in lignocellulose materials is important to understand changes in cellulase accessibility and reactivity resulting from hydrothermal deconstruction, to allow development of strategies to maximise bioethanol process efficiencies. To achieve progress, wheat straw lignocellulose and comparative model wood cellulose were characterised following increasing severity of hydrothermal treatment. Powder and fibre wide-angle X-ray diffraction techniques were employed (WAXD), complemented by enzyme kinetic measurements up to high conversion. Results: Evidence from WAXD indicated that cellulose fibrils are not perfectly crystalline. A reduction in fibril crystallinity occurred due to hydrothermal treatment, although dimensional and orientational data showed that fibril coherency and alignment were largely retained. The hypothetical inter-fibril spacing created by hydrothermal deconstruction of straw was calculated to be insufficient for complete access by cellulases, although total digestion of cellulose in both treated straw and model pulp was observed. Both treated straw and model pulps were subjected to wet mechanical attrition, which caused separation of smaller fibril aggregates and fragments, significantly increasing enzyme hydrolysis rate. No evidence from WAXD measurements was found for preferential hydrolysis of non-crystalline cellulose at intermediate extent of digestion, for both wood pulp and hydrothermally treated straw. Conclusions: The increased efficiency of enzyme digestion of cellulose in the lignocellulosic cell wall following hydrothermal treatment is a consequence of the improved fibril accessibility due to the loss of hemicellulose and disruption of lignin. However, incomplete accessibility of cellulase at the internal surfaces of fibrillar aggregates implies that etching type mechanisms will be important in achieving complete hydrolysis. The reduction in crystalline perfection following hydrothermal treatment may lead to an increase in fibril reactivity, which could amplify the overall improvement in rate of digestion due to accessibility gains. The lack of preferential digestion of non-crystalline cellulose is consistent with the existence of localised conformational disorder, at surfaces and defects, according to proposed semicrystalline fibril models. Cellulases may not interact in a fully selective manner with such disordered environments, so fibril reactivity may be considered as a function of average conformational states.